Living Conditions Influence Psychological Distress of Migrants in Long-Term Imprisonment - Lutz, Maximilian; Streb, Judith; Dudeck, Manuela (Frontiers in Psychiatry, 2019)
Background: Serving a long-term prison sentence places a heavy psychological burden on inmates. The concept of salutogenesis and the psychological stress model developed by Lazarus indicate that people can handle difficult situations if they are able to use their resources in a way that makes them feel confident that things will work out as well as can reasonably be expected. However, during long-term imprisonment inmates often have restricted access to potential coping strategies, such as close and trusting relationships. Because of migration-related difficulties, such as poor local language skills and experiences of discrimination, migrants in long-term imprisonment probably experience even more psychological distress than native citizens. Aims: The aim of the study was to compare the amount of psychological distress in migrants and native citizens in long-term imprisonment. In addition, we investigated whether any aspects of living conditions in prison reduce psychological distress. Methods: From the 1101 participants in the European Union (EU) project “Long-term imprisonment and the issue of human rights in member states of the EU,” we chose 49 migrants, defined as people born in a different country from where they were imprisoned, and 49 native citizens matched for prison, age (+/- 5 years), and index offense. The participants completed a questionnaire that included the Brief Symptom Inventory (BSI) and 128 items from a revised version of the Mare-Balticum prison survey. Data were analyzed by multilevel regression models. Results: Native citizens reported higher psychological distress than migrants. However, multilevel regression analyses showed that poor relationships with fellow inmates and increased fear of crime were significant predictors of increased psychological distress in migrants only. Conclusions: Being a migrant by itself does not lead to increased psychological distress in prisoners. This finding can be explained by the so-called healthy immigrant effect. However, migrants experience psychological distress when prisons are not safe and when they do not have close and trusting relationships with fellow inmates.